The Role of Mediators in Assisting in Settlement Civil Cases in Court - Habib, Yahya Abdul; Supriyatna, Dadang (International Journal of Business, Law, and Education, 2024)
The implementation of Mediation is regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures and has been carried out in accordance with applicable provisions starting from the pre-mediation stages, the mediation process, mediation reaching an agreement, mediation not reaching an agreement, and the end of the mediation. The mediator has a role as a neutral party who can perform a role according to his capacity with a number of skills, which are obtained from education, training and experience in resolving conflicts or disputes. Meanwhile, its function is to improve various communication weaknesses between the parties which usually have obstacles and psychological barriers, as well as encouraging the creation of a conducive atmosphere for starting negotiations, providing insight into the process and substance of ongoing negotiations, clarifying substantial issues and respective interests. each of the parties. The obstacle found in the mediation process was that the parties felt that their legal interests were not being met, as a result there was no meeting of mind and agreement to resolve the problem based on the principle of a win-win solution. The solution to overcome obstacles in mediation is Article 13 paragraph (1) PERMA No.1 In 2016, basically a Mediator is a person who is not a Judge who has received and obtained a Mediator certificate from an institution that has been accredited by the Supreme Court, however there are exceptions to this article which in the previous regulations,  namely PERMA No. 1 of 2008 Article 5 paragraph (2) is also regulated, which provides leeway if in a judicial environment there is no certified Mediator, then the Judge who is in that judicial environment based on the decision of the Chief of Court can become a Mediator